The Characteristics Of Computer Vision Syndrome Incidence In Medical Students At Baiturrahmah University Batch Of 2023 - Lassie, Naima; Mawida, Rampak; Nurwiyeni, Nurwiyeni; Hondrizal, Hondrizal; Adilla, Chandra; Rustam, Raihana (Oshada, 2024)
Computer Vision Syndrome (CVS) is an eye disorder caused by excessive screen time, which has become increasingly unavoidable in the digital era, particularly among medical students. This study aimed to determine the characteristics of CVS incidence among medical students of Baiturrahmah University, batch of 2023. Employing a descriptive approach, the study included 73 students selected using a purposive sampling technique, with univariate data analysis conducted through the SPSS program. The results revealed that 51 respondents (69.9%) were female, with 59 respondents (80.8%) using more than two devices daily. All respondents (100%) reported daily monitor usage exceeding four hours, categorized as unsafe screen time, and 62 respondents (84.9%) maintained an unsafe viewing distance from their monitors. Despite these findings, the majority of respondents (95.9%) did not experience CVS symptoms based on CVS-Q scores. These results suggest that while prolonged screen time and unsafe device usage are prevalent, they do not necessarily correlate with CVS incidence in this population